2020
DOI: 10.1111/jora.12582
|View full text |Cite
|
Sign up to set email alerts
|

The Gratification of Psychological Needs and Well‐Being Among Turkish Adolescents: An Examination of Direct and Indirect Links

Abstract: Based on the self‐determination theory (SDT), the present study tested a mediational model in a cross‐sectional data and found that gratification of basic psychological needs (GBPN; autonomy, relatedness, and competence) in adolescents’ relationships with their mother and father is linked with wellness (life satisfaction, problem‐solving confidence, and anxiety), through family cohesion, and disclosure and secrecy from mother. Adolescents (N = 1,097; 61.6% girls, Mage = 15.12, SD = 0.64; range = 14–16 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Children’s and adolescents’ happiness was positively correlated with family cohesion and intimacy [ 7 , 28 , 44 , 115 , 116 , 117 , 118 , 119 , 120 ]. Therefore, children who perceived a less cohesive atmosphere at home reported lower life satisfaction and higher negative affect [ 121 ], which precipitated negative thoughts towards people and events (i.e., hostility).…”
Section: Resultsmentioning
confidence: 99%
“…Children’s and adolescents’ happiness was positively correlated with family cohesion and intimacy [ 7 , 28 , 44 , 115 , 116 , 117 , 118 , 119 , 120 ]. Therefore, children who perceived a less cohesive atmosphere at home reported lower life satisfaction and higher negative affect [ 121 ], which precipitated negative thoughts towards people and events (i.e., hostility).…”
Section: Resultsmentioning
confidence: 99%
“…In research with urban Turkish 13‐ to 19‐year‐olds and their parents, adolescents and parents perceived high levels of cohesion in their relationships, and they highly valued family interdependence, with parents of girls reporting higher expectations of family interdependence than parents of boys (Dost‐Gözkan, 2012, 2020). However, despite high levels of parental warmth and cohesion, in the study mentioned earlier, only half of Turkish adolescents reported sharing their problems with their families (APT, 2013).…”
Section: Adolescent–parent Relationships and Youth Well‐beingmentioning
confidence: 99%
“…This theory postulates that autonomy (the need to be volitional in one's decisions and actions), relatedness (the need for supportive relationships), and competence (the need to feel efficient in one's interactions with the environment) are the basic psychological needs that must be met for well‐being (Ryan & Deci, 2017). In one study, Turkish parents' fulfillment of the psychological needs of 14‐ to 16‐year‐olds from an urban area and diverse socioeconomic backgrounds was linked to greater family cohesion, disclosure, life satisfaction, and problem‐solving confidence, and to lower anxiety (Dost‐Gözkan, 2020).…”
Section: Adolescent–parent Relationships and Youth Well‐beingmentioning
confidence: 99%